High Sensitivity Magnetometers - Grosz, Asaf.; Haji-Sheikh, Michael J.; Mukhopadhyay, Subhas C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers, for the first time, an overview of nearly all of the magnetic sensors that exist today. The book is offering the readers a thorough and comprehensive knowledge from basics to state-of-the-art and is therefore suitable for both beginners and experts. From the more common and popular AMR magnetometers and up to the recently developed NV center magnetometers, each chapter is describing a specific type of sensor and providing all the information that is necessary to understand the magnetometer behavior including theoretical background, noise model, materials, electronics, design and fabrication techniques, etc.
Induction Coil Magnetometers -- Parallel Fluxgate Magnetometers -- Orthogonal Fluxgate Magnetometers -- Giant Magneto-Impedance Magnetometers -- Magnetoelectric Magnetometers -- Anisotropic Magnetoresistance (AMR) Magnetometers -- Planar Hall Effect Magnetometers -- MEMS Lorentz Force Magnetometers -- Superconducting Quantum Interference Device (SQUID) Magnetometers -- Planar Magnetometers -- Nonlinear Magneto-Optical Rotation Magnetometers -- Spin Exchange Relaxation Free (SERF) Magnetometers -- Helium Magnetometers -- Microfabricated Optically-Pumped Magnetometers.
Keywords: Electronics; Signal processing; Measurement; Measuring instruments; Electronics and Microelectronics, Instrumentation; Signal, Speech and Image Processing; Measurement Science and Instrumentation